Pengaruh Penerapan Asesmen Formatif di awal Pembelajaran terhadap Partisipasi dan Hasil Belajar Mahasiswa Geografi di Universitas Negeri Padang - Syafri Anwar (Journal of Education on Social Science (JESS), 2023)
The research objective was to determine the effect of formative assessment at the beginning of collage on student participation and learning outcomes. The next objective is to compare the effect of assessment formative objective test form (af-Otf) and assessment formative essay test form (afEtf) on student participation and learning outcomes. Research method is quantitative with a one-way Monova technique, consisting of X as an independent variable (formative assessment), Y1, Y2 as dependent variables (student participation and learning outcomes). The subject of research was 24 students who take Process and Result of Learning Outcome Assessment (Penilaian proses dan hasil belajar geografi (PPHBg). The students were divided into two groups and each group had 12 students, the first group of (af-Otf), and the second group of (af-Etf). Research result; 1) the overall average participation of students who were given (af-Otf) was higher than the (af-Etf). 2) The average learning outcomes of (af-Otf) and (af-Etf) were 74.54 (good), a student with (af-Otf) was 83.17 (very good), and (af-Etf) was 65.92 (fairly good). Multivariate test results prove that the effect of (af-Otf) and (af-Etf) is 69.80 (very strong), meanwhile, the comparative test result of t value is t = 2,250; p-value = 0.035/2<0,05 means the (af-Otf) is stronger than (af-Etf). The study proves that formative assessment before instruction by using objective assessment is more effective in increasing student participational learning outcomes than essay formative assessment.